Insights into the regulation of wild soybean tolerance to salt-alkaline stress - Cai, Xiaoxi; Jia, Bowei; Sun, Mingzhe; Sun, Xiaoli (Frontiers in Plant Science, 2022)
Soybean is an important grain and oil crop. In China, there is a great contradiction between soybean supply and demand. China has around 100 million ha salt-alkaline soil, and at least 10 million could be potentially developed for cultivated land. Therefore, it is an effective way for improving soybean production by breeding salt-alkaline tolerant soybean cultivars. Compared with wild soybean, cultivated soybean has lost a large number of important genes related to environmental adaptation during the long-term domestication and improvement process. Therefore, it is of great importance to identify the salt-alkaline tolerant genes in wild soybean, and investigate the molecular basis of wild soybean tolerance to salt-alkaline stress. In this review, we will summarize the current research regarding the salt-alkaline stress response in wild soybean. The genes involving in the ion balance and ROS scavenging in wild soybean were summarized. Meanwhile, we also give an overall introduction of key protein kinases and transcription factors that were reported to mediate the salt-alkaline stress response in wild soybean. Findings summarized here will facilitate the molecular breeding of salt-alkaline tolerant soybean cultivars.